2016
DOI: 10.7717/peerj.2737
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a novel vaccine against prevalent invasive multi-drug resistant strains ofStreptococcus pneumoniae

Abstract: Streptococcus pneumoniae is a pathogen that causes serious invasive infections, such as septicemia, meningitis and pneumonia in addition to mild upper respiratory tract infections. Protection from pneumococcal diseases is thought to be mediated mainly by serotype-specific antibodies to capsular antigens. Pneumococcal conjugate vaccine consists of sugars (polysaccharides) from the capsule of the bacterium S. pneumoniae that are conjugated to a carrier protein. Three pneumococcal conjugated vaccines, each direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…Our results support previous work results of Badawy and his colleagues who reported that serogroup 6 is considered one of the most common colonizers in asymptomatic children in Africa and the Middle East [28]. Our results also supported the results of some earlier Egyptian studies where they found that types 6A/6B were the most common isolated capsular type in Egyptian children [29,30]. In contrast, another study done in Egypt in 2020, found that serotype 1 predominates in clinical and nasopharyngeal samples of Egyptian children [27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results support previous work results of Badawy and his colleagues who reported that serogroup 6 is considered one of the most common colonizers in asymptomatic children in Africa and the Middle East [28]. Our results also supported the results of some earlier Egyptian studies where they found that types 6A/6B were the most common isolated capsular type in Egyptian children [29,30]. In contrast, another study done in Egypt in 2020, found that serotype 1 predominates in clinical and nasopharyngeal samples of Egyptian children [27].…”
Section: Discussionsupporting
confidence: 93%
“…The resistance rate to beta-lactam drugs (oxacillin) was 34% as it was detected in 11 out of the 32 isolates. Comparable results to the present study were obtained by previous Egyptian studies where susceptibility to penicillin, macrolides, clindamycin, tetracyclines, chloramphenicol, fluoroquinolones, and linezolid ranged between (15%-85%), (50%-78.9%), (64.5%-94.7%), (16.1%-68.4%), (75%-100%), (85%-100%), and (84%-100%) respectively [27][28][29][30].…”
Section: Discussionsupporting
confidence: 84%
“…The first group was received a dose of 1 μg of P. aeruginosa LPS vaccine; the second group was received a 0.1 ml vaccine containing 1 μg of K. pneumonia LPS; the third group was received a combined vaccine that contained 1 μg P. aeruginosa and 1 μg K. pneumonia LPS vaccine through intraperitoneal injection. The lowest safe and effective dose in the induction of immunization was detected at 1 μg of LPS (Bahy et al, 2016). Two control groups, one for each microorganism injected with saline, contain 1 mg alum ml −1 .…”
Section: Methodsmentioning
confidence: 99%
“…By self-assembling Ga 3+ with tannins, we successfully formed GaTa NPs (Figure S8a,b, Supporting Information). To avoid in vivo immune clearance, [21] we extracted CPs from S. pneumoniae, a bacterium known for its ability to colonize the lung, using a thermal enzymatic hydrolysis method. [22] The successful extraction of CPs was confirmed by an obvious absorption peak at 206 nm in the UV-vis spectrum (Figure 3b and Figure S8c, Supporting Information).…”
Section: Construction and Characterization Of Bioinspired Gata-cp@eto...mentioning
confidence: 99%